Evaluation of ASD Severity in Children Aged 2-6 Years Using the Assessment Treatment Evaluation Checklist - Neny Triana; Mohammad Sulchan; Maria Mexitalia; Maria Suryani (International Journal of Artificial Intelligence Research, 2022)
A child can be diagnosed with autism spectrum disorder (ASD) before they are two years old. Children with ASD will show symptoms of social interaction and communication disorders, repetitive behaviours, and an extremely narrow range of activities of interest. Early ASD treatment will result in significant improvement in ASD symptoms. The assessment treatment evaluation checklist (ATEC) instrument is a commonly used instrument to evaluate the severity of ASD after being given therapy. This study aims to evaluate the severity of ASD in children aged 2-6 years using the ATEC instrument. This study used a cross-sectional design. A total of 66 ASD children aged 2-6 years from the autism clinic selected by simple random sampling were involved in the study. ASD severity was measured with the ATEC instrument by therapists from the autism clinic. Data on respondent characteristics such as gender and age diagnosed with ASD were evaluated. One-way ANOVA test was used in this study. The overall ASD severity at age 2,3,4,5,6 years was 96.45, 99.50, 94.23, 94.83, 100.87 respectively (possible score range is 0-179). There was no difference in the severity of ASD in each age group of children 2-6 years (p=0.878). There is no difference in the severity of ASD in children aged 2-6 years. ASD children need appropriate action to improve the severity of ASD from an early age on an ongoing basis